Understanding foreign direct investment in East Asia - Willem Thorbecke; Nimesh Salike (Asian Development Bank Institute (ADBI), 2011)
We recount East Asia's experience with foreign direct investment (FDI). We document that, contrary to the Rybczynski theorem, capital flows in the region cause the host country's labor-intensive industry to expand and its capital-intensive industry to decline. We also present narrative evidence that sheds light on how FDI is affected by the host's country's locational advantages, whether Asian FDI is footloose, and how the PRC has become the center of Factory Asia. Finally, we show that the evolution of production networks in the region can be explained partly by changes in the service cost of linking geographically separated production blocks relative to the cost saving arising from slicing up the value chain.
Keywords: F21; F23; O53; 330; Direktinvestition; Faktorpreisausgleich; Faktorproportionentheorem; Ostasien